THE PHYSIOLOGY OF PHOTOPERIODIC SENSITIVITY AMONG PLANT SPECIES WITH DIFFERENT LIGHT PERIOD - E N Zubkova; T A Belova (RUDN Journal of Ecology and Life Safety, 2017)
The most important characteristic of the environment for vegetable organisms is the photoperiod - duration of daylight. Plant Responses to the day length (photoperiod conditions) is of great importance in the development of environmental monitoring, providing the necessary spatial and temporal regulation of physiological processes in plants and optimizing the processes of photosynthetic activity. Objective: To estimate the photoperiodic sensitivity of samples of Raphanus sativus, and to identify his reaction to the increase in the length of daylight hours in conditions of Central Black Earth region. Change the duration of daylight is largely affects the development of plants. In terms of the long lightday photoperiodic sensitivity radish Raphanus sativus in the Kursk region is manifested in the increased growth of above-ground parts of plants and development of the generative organs. When growing radishes in the Kursk region in the conditions of artificially shortened daylight hours the plant for a long time remained in a vegetative state. It is clear that the formation of the major root crops of radish with good taste must be his growing under short photoperiod. The best planting time for the Central Black Earth zone - the end of March-April and the end of July-August, when the daylight hours of about 10 hours. When growing plants during the long daylight crops is necessary to create an artificial shading.